2022
DOI: 10.1021/acs.iecr.2c02282
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Bifunctional Electrocatalytic Activities of La0.5Sr0.5Co0.2Fe0.8O3 in Reversible Single-Component Cells

Abstract: Perovskite La0.5Sr0.5Co0.2Fe0.8O3 (LSCF) usually acts as both cathode and anode in a reversible solid oxide cell (RSOC). It is found that the traditional preparation method can be improved to reduce the particle size, increase the specific surface area, and enhance the oxygen vacancy concentration of LSCF, further improving its bifunctional electrocatalytic activity toward oxygen reduction reaction (ORR) and hydrogen oxidation reaction (HOR). Compared with that of LSCF prepared by the traditional solid-state r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…While the MF and HF display a weak relation with the PH 2 . Similar to the dependence of each resistance at different frequency regions on PO 2 , the dependence of each resistance at different frequency regions on PH 2 can be expressed as R p – (PH 2 ) m . The m values represent the different reaction steps on the fuel electrode, and the relationship between them is listed in Table S2.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…While the MF and HF display a weak relation with the PH 2 . Similar to the dependence of each resistance at different frequency regions on PO 2 , the dependence of each resistance at different frequency regions on PH 2 can be expressed as R p – (PH 2 ) m . The m values represent the different reaction steps on the fuel electrode, and the relationship between them is listed in Table S2.…”
Section: Resultsmentioning
confidence: 99%
“…Similar to the dependence of each resistance at different frequency regions on PO 2 , the dependence of each resistance at different frequency regions on PH 2 can be expressed as R p − (PH 2 ) m . 44 The m values represent the different reaction steps on the fuel electrode, and the relationship between them is listed in Table S2. Specifically, in this work, m = −0.3126 at LF between 0 and −0.5, demonstrating that the reaction process at LF is a mixed process including charge transfer reactions and oxygen surface exchange.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…由于半导体材料同时参与阳极和阴极反应, 因此对 半导体材料的结构和活性有较高的要求 [10] . 在众多电 极材料中, 具有混合离子和电子导电性(MIEC)和优异 氧化还原能力的钙钛矿氧化物(如 Sr 2 Fe 1.5 Mo 0.5 O 6-δ 和 La 0.5 Sr 0.5 FeO 3 等)被广泛用作 RSOC 的阳极和阴极材 料 [11][12] .…”
Section: 引言unclassified
“…6,7 The ionic conductor plays the role of transporting oxygen ions in the cell, while the semiconductor material plays the role of a bifunctional (fuel oxidation and oxidant reduction) catalyst. 8,9 In addition, because the SCFC has no clear electrolyte/electrode interface, it can effectively reduce the interface resistance of the cell. Therefore, SCFCs can operate at lower operating temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…The traditional fuel cell is a three-layer structure. Zhu et al reported a new type of cell structure: single-component fuel cell (SCFC), which is composed of a semiconductor and ionic conductor material. , The ionic conductor plays the role of transporting oxygen ions in the cell, while the semiconductor material plays the role of a bifunctional (fuel oxidation and oxidant reduction) catalyst. , In addition, because the SCFC has no clear electrolyte/electrode interface, it can effectively reduce the interface resistance of the cell. Therefore, SCFCs can operate at lower operating temperatures .…”
Section: Introductionmentioning
confidence: 99%